Ni- and Cu-Promoted Fixation Reactions of Carbon Dioxide with Unsaturated Hydrocarbons - Mori, Takamichi; Kimura, Masanari (Synlett, 2025)
Carbon dioxide is a significant greenhouse gas and reducing carbon emissions to mitigate global warming poses a major challenge. The efficient utilization of carbon dioxide as a carbon resource requires the development of effective and straightforward synthetic strategies for C–C bond transformations. Recent studies have focused on transition-metal-catalyzed coupling reactions of carbon dioxide with soft nucleophiles such as alkynes, conjugated dienes, and various unsaturated hydrocarbons, demonstrating the formation of unsaturated carboxylic acids. This article describes carbon dioxide fixation reactions with unsaturated hydrocarbons promoted by Ni and Cu catalysts that we have recently developed. Notably, these reactions feature highly regio- and stereoselective C–C bond formation facilitated by key intermediates involving organometalloids.
Keywords: nickel; copper; carbon dioxide; organozinc; organoaluminum; organoboranes; dienes; alkynes